2011
DOI: 10.1590/s1413-80502011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Persistência e memória longa sazonal na série de desemprego da região metropolitana de São Paulo

Abstract: ResumoEste artigo aborda o tema da persistência na taxa de desemprego da região metropolitana de São Paulo. Foram utilizados modelos SARFIMA de integração fracionária para avaliar a dinâmica de absorção dos choques econômicos pela série de desemprego. A hipótese de histerese no desemprego foi avaliada usando os modelos de memória longa. Os resultados obtidos pelo arcabouço fracionário foram contrapostos aos do paradigma I (1) − I (0) e revelaram a incapacidade dos modelos tradicionais SARIMA de extrair correta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…Furthermore, for the unemployment series, all tests accepted the hypothesis of the presence of the trend component. In a similar study, but with a smaller number of observations (in the period from 1985 to 2010), Marques and Fava (2011) showed that the unemployment series in the Metropolitan Region of São Paulo presented seasonality and also a stochastic trend, being confirmed through of the ADF unit root test.…”
Section: Unemployment Rate In the Metropolitan Region Of São Paulomentioning
confidence: 71%
“…Furthermore, for the unemployment series, all tests accepted the hypothesis of the presence of the trend component. In a similar study, but with a smaller number of observations (in the period from 1985 to 2010), Marques and Fava (2011) showed that the unemployment series in the Metropolitan Region of São Paulo presented seasonality and also a stochastic trend, being confirmed through of the ADF unit root test.…”
Section: Unemployment Rate In the Metropolitan Region Of São Paulomentioning
confidence: 71%
“…Em que se pese alguma divergência de resultados em função de amostras diferentes, as estimativas têm apontando para uma constate de integração no intervalo entre zero (excluso) e 0,5 (incluso), principalmente no período pós Plano Real. Marques & Fava (2011), por sua vez, encontram suporte à hipótese de memória longa na média e no componente sazonal do desemprego na região metropolitana de São Paulo.…”
Section: Introductionunclassified